Application Of Data Mining In Grouping Data On The Need For Social Welfare Services (Ppks) At The Dharma Guna Center In Bengkulu - Wahyuni, Mera; Yulianti, Liza; Alinse, Rizka Tri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Sentra Dharma Guna Bengkulu is an institution under the auspices of the Ministry of Social Affairs of the Republic of Indonesia that provides social rehabilitation services for people with disabilities, including therapy (physical therapy and occupational therapy) and training. At Sentra Dharma Guna Bengkulu, data collection is carried out on PPKS (Social Welfare Service Recipients) every month to determine the development of the PPKS based on 5 (five) assessment aspects, namely physical aspects, spiritual aspects, psychological aspects, social aspects, and vocational aspects. Every month the development of PPKS Mentally Disabled (PDM) is assessed against 5 assessment aspects to determine whether PPKS is in the severe, moderate or mild group. The application of data mining in grouping data on Social Welfare Service Recipients (PPKS) at the Dharma Guna Bengkulu Center can help collect data and assess the development of PPKS, especially People with Mental Disabilities (PDM), can help analyze and group PPKS data, especially People with Mental Disabilities (PDM), and can provide information on the results of grouping PPKS data, especially People with Mental Disabilities (PDM) every month. From the test data used, namely PPKS data for People with Mental Disabilities (PDM) in October 2024 as many as 49 PPKS, the results of data grouping were obtained using the K-Means Clustering Method which has been divided into 3 groups. The number of Cluster C1 data (Severe Group) consists of 9 PPKS data, Cluster C2 (Moderate Group) consists of 26 PPKS data, and Cluster C3 (Light Group) consists of 14 PPKS data.